Study of gender equality in community based forest certification programmes in Nepal - Lewark, S.; George, L.; Karmann, M. (2011)
Gender equality has been studied in community based forest certification projects in two forest user groups in Nepal. contributing to an understanding of gender equality with a focus on participation of women in a forest certification project and on awareness levels of forest users. Experts from the project and local people were interviewed. Committee meetings were conducted and household interviews were also carried out. The results include information on the background and lives of respondents as well as the effects of forest certification on their lives today; on age, caste and occupation; attitudes of men and women regarding forestry and their opinions on conditions before and after forest certification; non-timber forest products (NTFP), Forest Stewardship Council (FSC) certification processes in Nepalese forests; forest committee meetings. This paper summarizes selected findings from George (2010); results and suggestions may serve to improve plights of forest users in Nepal.